VR scenarios to treat mental health - Deusdado, Leonel (2022)
Schizophrenia is characterized by delusions, hallucinations, anhedonia and apathy, and is a chronic mental illness, which still has no cure. It is diagnosed in three main groups, namely positive symptoms, negative symptoms, and cognitive symptoms, and affects the patient in major areas of life, such as work, interpersonal relationships, or self-care. The usual treatment is carried out with the help of antipsychotic med- ications, which mainly target the positive symptoms of the illness, but have little effect on the negative symptoms of schizophrenia. It is a disease that affects 1% of the population, and while it is not the most common of other mental disorders, it can be the most disabling. Virtual reality (VR) is increasingly used as a powerful auxiliary tool in rehabilitation. It al- lows an immersive audio-visual environment with high clinical relevance and robust validity, modernizing rehabilitation interventions, leading to improved motor function and biomechanical or diagnostic ability better than traditional methods used to treat patients under cognitive health. In this context, this paper addresses the design of virtual environments and computer simulations, providing the patient with an experience close to the real world, and allowing intensive repetition of essential tasks dur- ing the mental health rehabilitation process, with real-time feedback in a controlled and safe environment. Virtual reality (VR) is increasingly used as a powerful auxiliary tool in rehabilitation.